CATEGORIES AND FUNCTIONS OF ENGLISH TABOO WORDS IN THE FILM “BLINDSPOTTING” (2018) - Rizma Rizqina Muwahhida (UIN Alauddin Makassar, 2021)
The taboo word is a word that is avoided because it is felt to have a 'strong' meaning, so that some types of taboo words cannot just be spoken by anyone or anywhere. To overcome this, one usually chooses to use other words that are safer. This paper aims to determine the types of taboo words in the film “Blindspotting” based on Ronald Wardhaugh’s theory which divides them into several categories, namely: sex, death, excreation, bodily functions, religious matters, politics, mother-in-law, animals, and cultural matter, as well as the function of each taboo word in the film which he divides it into four functions, such as: showing contempt, drawing attention, being provocative or aggressive, and mocking authority. The method used to analyze this film is a qualitative descriptive method where the researcher describes, analyzes, and discusses the data in the film as it is in narrative form. The results showed that there are seven categories of taboo words in the film, included: sex, death, excreation, bodily functions, religious matters, animals, and cultural matter. The sex and bodily function are the most used category in the film, while the cultural matters is the least used. Of the four functions of Ronald Wardhaugh, All of them are found in the film.